2019
DOI: 10.1073/pnas.1903445116
|View full text |Cite
|
Sign up to set email alerts
|

Arm movements induced by noninvasive optogenetic stimulation of the motor cortex in the common marmoset

Abstract: SignificanceWhich brain area drives hand/arm movements after learning or brain injury? When does motor cortical activity generate appropriate hand/arm movements? To address these issues, it is necessary to manipulate motor cortical activity in a controlled manner. Optogenetic tools allow neuronal activity to be manipulated in a variety of animals, but forelimb movements in nonhuman primates have not previously been optogenetically induced or modulated. Here, we improved a method of optogenetic cortical stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 43 publications
0
38
0
1
Order By: Relevance
“…rotational behavior, speed, mobile time, mobile episodes, and distance traveled [17,18]. Recently, effects on single body parts have also been started to be investigated via video analysis [19]. To systematically investigate the effect of optogenetic stimulation in freely moving rats, we recorded the movements of three animals in four sessions, two sessions with 30 Hz laser burst frequency and two sessions with 10 Hz with a stimulation duration of 5 sec, 10% duty cycle.…”
Section: Neuronal Representations Of Behavioral States and Paw Trajecmentioning
confidence: 99%
“…rotational behavior, speed, mobile time, mobile episodes, and distance traveled [17,18]. Recently, effects on single body parts have also been started to be investigated via video analysis [19]. To systematically investigate the effect of optogenetic stimulation in freely moving rats, we recorded the movements of three animals in four sessions, two sessions with 30 Hz laser burst frequency and two sessions with 10 Hz with a stimulation duration of 5 sec, 10% duty cycle.…”
Section: Neuronal Representations Of Behavioral States and Paw Trajecmentioning
confidence: 99%
“…Remarkable results have been achieved; for instance, it was demonstrated that dendritic activity recorded optically from the motor cortex of monkeys transfected to express a fluorescent activity reporter in excitatory neurons could reliably be employed to predict the direction of the arm movement [ Trautmann et al, 2019 , preprint article ]. Manipulating cerebellar neurons via optogenetics could drive saccade movements ( El-Shamayleh et al, 2017 ), while performing similar recordings and stimulation in the motor cortex of marmoset monkeys has been employed to investigate the neural dynamics of arm movements ( Ebina et al, 2018 , 2019 ).…”
Section: Observing and Hacking The Animal Brain During Motor Behaviormentioning
confidence: 99%
“…Studies in the awake marmoset have predominantly been performed under head fixation. This has been used for various recording and stimulation approaches, like electrocorticographic (Hung et al, 2015), extracellular microelectrode (Johnston et al, 2018;Remington et al, 2012), and intracellular (Gao et al, 2016;Gao and Wang, 2019) neuronal recordings, microstimulation (Selvanayagam et al, 2019), fMRI (Belcher et al, 2013;Hung et al, 2015;Liu et al, 2013;Schaeffer et al, 2019), as well as calcium imaging (Mehta et al, 2019;Yamada et al, 2004) and optogenetics (Ebina et al, 2019;Macdougall et al, 2016).…”
Section: Introductionmentioning
confidence: 99%